The Paradoxical Discourse of Language and Silence in Some Contemporary North-American Texts on the Arctic - Brøgger, Fredrik Chr. (Nordlit, 2012)
The Arctic has often been regarded (its various indigenous groups notwithstanding) as a desolate and silent void to be explored and defined by Euro-westerners, usuallyin terms of a masculine competitive ethos and an ethnocentric rhetoric of WesternEnlightenment and progress. Surprisingly, even many Norwegian arctic expeditionsof our own time tend to embody similar narratives of conquest and athletic prowess.Among contemporary North-American writers, however, this kind of discourse isprofoundly questioned, particularly by focusing on the problematic function oflanguage itself in our constructions of the Arctic. This article focuses on three North-American books in which the issue of the Euro-western linguistic appropriation ofthe Arctic, its natural environment as well as its peoples, is a major concern; they areall reflections on the issues of writing and silence with reference to the far north. Thethree books are: Barry Lopez' Arctic Dreams: Imagination and Desire in a NorthernLandscape (1987), Aritha van Herk's Places Far from Ellesmere (1990), and JohnMoss' Enduring Dreams: An Exploration of Arctic Landscape (1996). Central in allof them is the following issue: how to make the wordless landscape or the alienculture speak from under, as it were, the enormous compilation of centuries of Eurowesterntext. The article discusses four major strategies by which these three booksattempt to counteract and subvert earlier Euro-western ethnocentric and monologicnarratives of the Arctic: by the inclusion of feminine and indigenous voices; by thelegitimation of the sensuous life-world of the Arctic itself; by the self-reflexivesubversion of the authority of the language of their own texts; and by the use of astyle of paradox and contradiction. By way of such techniques, the books above try to create more open, dialogic and pluralistic readings of the Arctic.